Optimal Energy Management for Zero-Emission High-Speed Passenger Vessels - Najjaran, Samieh; Skjetne, Roger; Godø, John Martin Kleven (Volume 5: Ocean Engineering, 2023)
To comply with IMO’s regulations on reduced emissions, the maritime industry is investigating various alternatives to achieve zero-emission high-speed passenger vessels (HSPVs). In this work, optimal loadsharing is studied for a given vessel with a zero-emission hybrid driveline with a fuel cell (FC) and a battery. The further aim is to include this as part of a computation model to assess feasibility of zero-emission solutions for passenger transport connections under study along the coast of Norway. A dynamic programming (DP) algorithm is derived to provide the global optimal solution of the loadsharing problem. This will serve as a benchmark for other and more computationally efficient optimization algorithms to be feasible for runtime applications. Here we formulate an alternative optimal loadsharing model based on a linear program (LP) and compare that to the DP. The proposed LP and DP are applied to a numerical model for an existing HSPV operating along a given route. AIS data is used to extract the route information and power load profile of the vessel. The results demonstrate a step towards an overall methodology for assessing the feasibility of a vessel and an onboard propulsion and power system to allow for zero-emission passenger transport. Optimal Energy Management for Zero-Emission High-Speed Passenger Vessels publishedVersion